Digital Heritage Interpretation: Learning From the Realm of Real-World - Rahaman, Hafizur; Tan, B. (2017)
Heritage interpretation is often used to indicate the storylines adapted to help visitors to engage with and understand historical sites or artefacts. However, until now we hardly find any noteworthy scholarly works, charter, and critical discourse on the theory and methodology of interpretation in the field of Digital Heritage. Praxis limited by such theoretical underpinning, and at the same time the unwitting obsession with technology as a way out for better interpretation is leading most of the digital heritage projects to become descriptive and ocular-centric. Although technologies and tools like game-engines, multi-player virtual environments, haptic devices, augmented visualizations and immersive displays are being used to accentuate experience and visual fidelity, nevertheless, many scholars argue that technology alone can only provide partial interpretation. This paper raises the demands for an interpretive method for digital heritage and proposes some guidelines based on interpretation theories and scholarly materials from the real-world heritage domain.